TOURIST, ECONOMIC INDICATORS AND THE EVALUATION OF THE EFFECTIVENESS OF CLUSTERS THERE ARE PROBLEMS (International journal of artificial intelligence, 2026)
the article content of the cluster approach in the field of tourism and economic role in the development of its territorial illuminated. The assessment of the effectiveness of the proposed a system of indicators which many tourism clusters. Also, to analyze systemic problems in the process and eliminate them klasterlashuv scientific-practical recommendations put forward.